Establishment of authenticity and typicality of sugarcane honey based on volatile profile and multivariate analysis - Silva, Pedro (2019)
Sugarcane honey (SCH) is a black syrup produced in Madeira Island widely known for their excellent quality being used in traditional pastry and confectionery. However, its notoriety has been affected by circumstances in which some producers do not guaranty the product quality. The purpose of this study was to establish, for the first time, the volatomic profile of SCH produced by certified and non-certified producers in order to define their authenticity and typicality as useful platform to ensure SCH safety, protect consumer interests and fight the continuous problems of food fraud and adulteration. Solid-phase microextraction in headspace mode (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) was applied as high throughput approach for extraction, separation and identification of SCH volatile compounds. The extraction technique was optimized for nature of stationary phase, extraction temperature, extraction time, and validated according with IUPAC and AOAC guidelines. Different volatomic fingerprints for SCH from certified and non-certified producers were recognized, being identified up to 87 volatile organic compounds (VOCs) belonging to distinct chemical classes, mainly aldehydes, alcohols, ketones and furans. One-way ANOVA analysis showed the existence of 18 VOCs with statistically significant differences between volatile profiles from certified and non-certified producers. Principal component analysis (PCA) and linear discriminant analysis (LDA) differentiate and discriminate the samples from both type of producers. According to the obtained results, the followed strategy revealed an effective way to establish the authenticity and typicality of SCH, providing useful information to producers that might therefore be used to improve the SCH quality and a powerful platform to promote a European certification application.